2016
DOI: 10.1371/journal.pone.0165391
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Perception of Audiovisual Distance: Bayesian Causal Inference and Other Models

Abstract: Studies of audiovisual perception of distance are rare. Here, visual and auditory cue interactions in distance are tested against several multisensory models, including a modified causal inference model. In this causal inference model predictions of estimate distributions are included. In our study, the audiovisual perception of distance was overall better explained by Bayesian causal inference than by other traditional models, such as sensory dominance and mandatory integration, and no interaction. Causal inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 43 publications
1
8
1
Order By: Relevance
“…Therefore we conclude that in the laboratory environment, in which visual cues do not comply with auditory cues, the former play a minor role. This agrees with findings in [29,30] showing that sensory interactions, e.g., vision vs. audition, include a weighting process where the most reliable cue contributes the most to the multi-sensory percept. Figure 14 shows the results for the ASW rating task of the second experiment.…”
Section: Auditory Distancesupporting
confidence: 91%
“…Therefore we conclude that in the laboratory environment, in which visual cues do not comply with auditory cues, the former play a minor role. This agrees with findings in [29,30] showing that sensory interactions, e.g., vision vs. audition, include a weighting process where the most reliable cue contributes the most to the multi-sensory percept. Figure 14 shows the results for the ASW rating task of the second experiment.…”
Section: Auditory Distancesupporting
confidence: 91%
“…Imprecision of auditory distance perception relative to visual distance perception. Elegant modeling work by Mendonça et al (2016) clearly demonstrates that visual capture in distance is explainable based on the relative imprecision of auditory distance perception relative to visual distance perception. This concept is a fundamental aspect of other probabilistic models of multisensory integration which result in more weight being given to perceptual modalities that produce more precise estimates of a given perceptual quantity ( Ernst and Banks, 2002 ; Alais and Burr, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“… Mendonça et al (2016) applied this type of probabilistic explanation to visual capture in the distance dimension by evaluating a number of different probabilistic models. Although in general, this approach can explain situations both where visual capture in distance is ( Gardner, 1968 , 1969 ; Mershon et al, 1980 ) and is not observed ( Zahorik, 2001 ; Calcagno et al, 2012 ), the models evaluated by Mendonça et al (2016) do not incorporate a fundamental aspect of perceived auditory space: that perceived distance is non-linearly related to physical distance. Best evidence suggests that perceived distance is instead logarithmically related to physical sound source distance (see Zahorik et al, 2005 for a meta-analysis of the auditory distance perception literature).…”
Section: Introductionmentioning
confidence: 99%
“…[18: 417] Such probabilistic perspectives have gained popularity in recent years as notions of sensory dominance fade. The Maximum Likelihood Estimation (MLE) model which assumes that the perceptual weighing process is statistically optimal, is proving particularly popular [33].…”
Section: 26mentioning
confidence: 99%